Crônicas do “gauchês”: proposta de sequência didática com uso do instagram - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This study presents the development and theoretical-descriptive analysis of a didactic sequence designed to teach diatopic linguistic variation, focusing on the Gaúcho dialect, through the production of chronicles intended for circulation on Instagram. The research aims to construct a didactic pathway that integrates reading, oral practices, linguistic analysis, and writing, in alignment with the dialogic perspective of language and the guidelines of the Brazilian National Common Curricular Base (BNCC). It adopts a qualitative approach, basic in nature and exploratory in scope, grounded in specialized bibliography and in the production of a didactic sequence structured according to the model proposed by Lopes-Rossi (2002). The analysis shows that working with discourse genres, multiliteracies, and regional linguistic repertoires supports the understanding of language as a social, historical, and heterogeneous phenomenon. The results indicate that the proposal enhances students’ knowledge of linguistic variation, supports the confrontation of linguistic prejudice, and brings Portuguese language teaching closer to contemporary practices of textual circulation, particularly those present on social media.
Keywords: Variação linguística; Sequência didática; Crônicas; Gauchês; Instagram; Linguistic variation; Chronicles; Gauchês; Instagram; Didactic sequence; LINGUISTICA, LETRAS E ARTES